Application of multi-beam bathymetry system in shallow water area. Issue 1 (1st February 2023) - Guo, Qiang; Fu, Chuanyu; Chen, Yikang; Zhang, Yu
Abstract: Multi-beam bathymetry technology plays an important role in ocean, river and lake surveying and mapping. According to the measurement principle and technical requirements of MS8200 multi-beam bathymetry system, this paper introduces the composition and working principle of the system, the installation and calibration of the system, and the data in the post-processing process, the sea area and terrain characteristics near Wenchang Qinglan Port are taken as the research object to discuss the dual multi-beam bathymetric technology and data processing process, and compare the data of single multi-beam in the same sea area. The research results show that the dual probe of multibeam bathymetry system can better reflect the topographic features of the seafloor compared with the single probe, and shorten the time of mapping, reduce the labor intensity and improve the measurement efficiency, and provide data reference for the stability and reliability evaluation study of the dual probe of multibeam bathymetry system.